Revision of the Oriental and eastern Palaearctic planthopper genus Saigona Matsumura, 1910 (Hemiptera: Fulgoroidea: Dictyopharidae), with descriptions of five new species - Liang, Ai-Ping; Song, Zhi-Shun (Zootaxa, 2006)
The Oriental and eastern Palaearctic planthopper genus Saigona Matsumura, 1910 is revised to include nine species including five new species: S. capitata (Distant, 1914) (Indo-China, S.W. China: Yunnan), S. fulgoroides (Walker, 1858) (S. China, Sumatra, Borneo), S. fuscoclypeata sp. nov. (C. China: Shaanxi, Hubei and Gansu), S. henanensis sp. nov. (C. China: Henan), S. latifasciata sp. nov. (S.W. China: Yunnan), S. robusta sp. nov. (C. China: Hubei), S. sinicola sp. nov. (C. China: Shaanxi), S. taiwanella Matsumura, 1941 (China: Taiwan), and S. ussuriensis (Lethierry, 1878) (Russian: Far Eastern Region, Japan, Korea, N.E. China: Jilin, Heilongjiang). Two new generic and one new specific synonyms are recognized: Saigona Matsumura, 1910 = Leprota Melichar, 1912 syn. nov. = Piela Lallemand, 1942 syn. nov.; S. fulgoroides (Walker, 1858) = Piela singularis Lallemand, 1942 syn. nov. S. capitata (Distant, 1914) is recorded from China for the first time. The genus and its included species are described and illustrated. Photographs of the adults of all known species except S. taiwanella are presented. Descriptions of the genus and its included species are provided together with structural illustrations. A key to the known species of Saigona is provided.